(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Selected anaesthetic indices of, and the heart rate, respiratory rate and rectal temperature responses of 6 healthy rabbits to the intramuscular administration of 2mg/kg midazolam and 25 mg/kg ketamine alone (MK) and combined with 4mg/kg tramadol (MKT) were evaluated over a 60-min observation period. Time to loss of righting reflex with MKT (1.7±0.3min) was significantly (p˂0.05) shorter than with MK (4.2±1.5min). Duration of recumbency with MKT (76.8±5.1min) and MK (77.8±3.6min) were similar. Time to standing with MKT (9.3±1.1min) was shorter than with MK (15.2±2.4 min). Mean heart rates ranged from 204.7±13.0 to 257.5±3 beats/min with MK, and from 207.3±4.6 to 238.8±8.7 beats/min with MKT. Mean respiratory rates ranged from 33.8±6.2 to 64.3±15.0 breaths/min with MK; from 36.2±2.5 to 54.0±8.6 breaths/min with MKT. Mean temperature ranged between 38.0±0.2 and 38.9±0.2oC with MK and between 37.9±0.3 and 39.1±0.1oC with MKT. Neither MK nor MKT produced analgesia. It was concluded that although the inclusion of tramadol did not produce analgesia, it produced a faster onset of action than midazolam-ketamine alone. Midazolam-ketamine-tramadol will be useful for non-painful procedures where rapid drug action is needed.